Indocyanine green fluorescence angiography as a predictor of distal flap necrosis in latissimus dorsi free flaps - Didzun, Oliver; Thomas, Benjamin; Panayi, Adriana C.; Broichhausen, Sonja; Osenegg, Sophie; Falkner, Florian; Hundeshagen, Gabriel; Knoedler, Samuel; Knoedler, Leonard; Vollbach, Felix Hubertus; Kneser, Ulrich; Gazyakan, Emre; et al. (Microsurgery, 2025)
Background Vascularization of the distal latissimus dorsi (LD) muscle flap determines the success of the procedure, particularly in large defects. Failure due to distal flap necrosis can necessitate reoperation and increase mortality. Indocyanine green fluorescence angiography (ICGFA), as a modality that allows for intraoperative imaging of fasciocutaneous flap perfusion, has revolutionized free flap surgery. Evidence of use in muscle flap perfusion assessment is lacking. We investigate the efficacy of ICGFA in predicting distal flap necrosis in large LD free flaps. Methods We prospectively recorded all cases of large LD free flap reconstruction (surface area > 250 cm2) at our institution (01/2018-12/2022). Patients were grouped according to the intraoperative perfusion assessment: ICGFA or clinical judgment. The primary outcome was distal flap necrosis > 5% of the total flap. Secondary outcomes included reoperation and total operation time. Multivariable analyses were applied to identify independent risk factors. Results A total of 107 patients with mean age of 57 ± 18 years and BMI of 29 ± 6 kg/m2 were included. Thirty-six patients (34%) underwent ICGFA. ICGFA was associated with a significant reduction in distal flap necrosis (18.3% vs. 2.8%, OR: −0.15, 95% CI: −0.29 to −0.02; p = 0.03) and reoperation (40.8% vs. 19.4%, OR: −0.21, CI: −0.41 to −0.02; p = 0.03), with no prolongation of the operation time (158 ± 63 vs. 191 ± 91 min, p = 0.39). Conclusion ICGFA is associated with increased success of large LD free flap reconstruction, allowing a more accurate and reliable assessment of perfusion. This highlights the immense potential of ICGFA as a clinical standard, surpassing its application solely in fasciocutaneous free flap surgery and, showcasing its efficacy in free muscle flap procedures. Registration: This study has been registered at https://www.researchregistry.com (identification number: researchregistry9496).